Perceptions on male nurse among health care workers in Hospital Tengku Ampuan Afzan (HTAA) - Al-Araji, Laith Issa Yassin; Halek, Aminatuzzahrah A. (2008)
The entering of men into nursing is widely spread in around the world; Malaysia is not excluded from this scenario. The former dominated profession by female now will become free-gender occupation. As the productions of male nurse keep increasing into health care institution, the researcher feels the need to know the other health care workers’ perception on male nurse. The study had done in HTAA to find out the health care workers namely are from the nurses, doctors, medical assistants, and hospital attendants’ perception on male nurse. This cross-sectional study was conducted in form of questionnaire and all the data obtained were analyzed. There were 226 respondents participated in this study which revealed that majority strongly accept the upcoming of male nurse into health care sector. This study also found out that there is no significant between age and gender of health care workers with the degree of acceptance on male nurse. Whereas, the occupation of health care workers and experienced working with male nurse showed the significant relationship. Moreover, majority of the respondents agreed that patient had gender preference of health care workers and disagreed that the gender issues arise in health care institution. In short, the findings of this study reflect that the health care workers were aware with the upcoming of male nurse in the health care setting.